Analyse onomasiologique du français radiophonique algérien - Nabil Sadi (Multilinguales)
Onomasiology is a semantic study consisting of an approach which starts from the idea of the concept, to study its various expressions in a language. This research constitutes an onomasiological study of the exogenous elements contained in the interactional radiophonic discourse of Alger-chaîne 3. We propose to establish a typology of the code-switching, then to move to their lexematic features in order to establish their different realizations.